Effectiveness of Marketing Initiatives in Improving "lead-to-sales" Conversion of Steel Rebar in Retail Segment of India - Dasgupta, Biswadeb (Global journal of Business and Integral Security, 2023)
This research aims to develop a structured framework for capturing & analyzing historical data on the impact of various marketing initiatives in improving the sales revenue of Steel Rebar in the retail segment of India. The need for this research is evident in making objective analysis and allocation of marketing budget among various alternatives. Quantitative research technique is used for analysis and establishing relationship between initiatives and sales. Historical data on marketing initiatives and their impact on sales revenue were merged with the effectiveness survey response of key stakeholders (consumers/Channel partners/Marketers) to arrive at the overall effectiveness score of each marketing initiative. The framework and the model developed should serve as a decision support tool and facilitate the selection of marketing alternatives under budget constraint scenarios. Although the model’s insights were derived from studying one of India’s leading retail brands in the home construction segment, it can be applied to similar brands and product categories to facilitate decision-making and gaining valuable insights.